A Review of 20 Years of Research on Overdiagnosis and Underdiagnosis in the Rhode Island Methods to Improve Diagnostic Assessment and Services (MIDAS) Project. (February 2016) - Zimmerman, Mark
The Rhode Island Methods to Improve Diagnostic Assessment and Services (MIDAS) project represents an integration of research methodology into a community-based outpatient practice affiliated with an academic medical centre. The MIDAS project is the largest clinical epidemiological study using semi-structured interviews to assess a wide range of psychiatric disorders in a general clinical outpatient practice. In an early report from the MIDAS project, we found that across diagnostic categories clinicians using unstandardized, unstructured clinical interviews underrecognized diagnostic comorbidity, compared with the results of semi-structured interviews. Moreover, we found that the patients often wanted treatment for symptoms of disorders that were diagnosed as comorbid, rather than principal, conditions. This highlighted the importance, from the patient's perspective, of conducting thorough diagnostic interviews to diagnose disorders that are not related to the patient's chief complaint because patients often desire treatment for these additional diagnoses. While several of the initial papers from the MIDAS project identified problems with the detection of comorbid disorders in clinical practice, regarding the diagnosis of bipolar disorder we observed the emergence of an opposite phenomenon—clinician overdiagnosis. The results from the MIDAS project, along with other studies of diagnosis in routine clinical practice, have brought to the forefront the problem with diagnosis in routine clinical practice. An important question is what do these findings suggest about the community standard of care in making psychiatric diagnoses, and whether and how the standard of care should be changed? The implications are discussed.